Mathematical Quest as a Learning Activity - Quchqarova Mahmuda Adkhamjonovna; Yunusova Zarnigor (Zien Journals, 2022)
The article is devoted to the use of gaming technologies in teaching mathematics. As one of the modern forms of this activity, the use of a mathematical quest is proposed. The article discusses the features of using the quest in teaching mathematics
Keywords: mathematical quest; game technology; live quests